CARA MEMPEROLEH MODAL USAHA MELALUI PIHAK KETIGA - Hendy Satria; Tommy Munaf; Ranat Mulia Pardede; Kevin, Kevin; Okvita Adhayani; Elvina, Elvina; Hasan Albana; Zydyan Zahara Marsya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The community service activity (PPM) AT STIE Pembangunan Tanjungpinang refers to the starategie plan outlined in the reaserch ,aster plan (RIP) of the STIE Pembangunan Tanjungpijnang. Service strategie plan, the location of the activitywhich is located in Teluk Sebong sub=district which is in Bintan Regency which is geographically located on the island of Bintan. The total area of Teluk Sebong district is 337,65 km2. UMKM is a from of community small bucinnes whose founders are based on someone’s initiatifve. The emergence of many MSMEs does not mean that there are no problems that occur in this MSMEs, many factors are encountred when going out into the field, one of which is in the capital sectore, many parties frome these MSMEs are hindered by capital, and do not know how to solve this problem, this is due to the lack of knowladge possessed by the MSMEs parties, so here we are trying to find a way out by imparting our knowladge to these MSME parties by explaining how to borrow capital through third parties through banking agencies, from the result of the researchh show that the target MSMEs already understand and understand the education and application thathas been given regarding this party capital loans